A critical companion to Old Norse literary genre - Sif Ríkharðsdóttir,Bampi, Massimiliano,Larrington, Carolyne (D.S. Brewer, 2020)
A comprehensive guide to a crucial aspect of Old Norse literature.
Title from publisher's bibliographic system (viewed on 13 Oct 2020)
Keywords: Altnordisch; Literatur; Literaturgattung